PENGOBATAN PERSONALISTIK GURU SIBASO TERHADAP PELAKU ASUSILA DI OBJEK WISATA DANAU LAU KAWAR KABUPATEN KARO - Claudia, Yola; Puspitawati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
The objective of this study is to analyze the treatment process carried out by Guru Sibaso, the community's rationale in electing Guru Sibaso to administer personalistic treatment for immoral tourists, and the community's perception of Guru Sibaso's personalistic treatment practices. The research method employed is qualitative, employing a descriptive approach. The theoretical framework employed in this study is ethnomedicine theory, as proposed by Foster & Anderson. The research was conducted at Lake Lau Kawar, and data were collected through observation, interviews, and documentation. The results indicated that tourists who violate social norms at Lake Lau Kawar frequently encounter supernatural disturbances, which are perceived as a form of retribution from the supernatural entities believed to protect the lake. In the treatment process, Guru Sibaso engages in spiritual communication with jinujung (dead ancestral spirits) and utilizes natural ingredients in the practice of personalistic medicine. Despite the advent of modern medicine, local communities continue to place their trust in the efficacy of Guru Sibaso's personalistic medicine. Beyond its role as a healing modality, this practice functions as a form of social control, contributing to the maintenance of customary norms and spiritual values within the context of the tourist environment.